Hydrogen production from ammonia decomposition over Ru-rich surface on La2O2CO3-Al2O3 catalyst beads - AHREUM KIM; Cha Jun Young; Kim, Jin Su; Ahn,Chang-Il; Kim, Yongmin; Jeong, Hyang soo; Choi, Sun Hee; Nam, Suk Woo; Yoon, Chang Won; Sohn, Hyuntae (Elsevier BV, 2023)
Three ruthenium-supported catalyst beads (Ru/Al2O3, Ru/La2O3-Al2O3 and Ru/La2O2CO3-Al2O3) were synthesized and tested for ammonia decomposition. The catalytic activity of the Ru/La2O2CO3-Al2O3 beads was significantly higher than that of the Ru/Al2O3 and Ru/La2O3-Al2O3 beads. This was primarily attributed to the addition of La, which encouraged electron donation from the bead surface to the Ru particles, increasing the rate of N2 desorption. In particular, a higher Ru surface concentration was achieved over the boundary layer of La2O2CO3 compared with La2O3. This is thought to be a result of steric hindrance, with the crystalline surface of La2O2CO3 acting as a structural stabilizer to significantly limit the penetration of Ru particles into the catalyst bead core. SEM-EDS line scanning of transverse sections of the catalyst beads confirmed a higher Ru concentration on the surface of the catalyst beads for Ru/La2O2CO3-Al2O3 compared with Ru/La2O3-Al2O3 and Ru/Al2O3. In fact, the ratio of surface/bulk Ru concentration in Ru/La2O2CO3-Al2O3 was more than twice that of Ru/Al2O3 at equal Ru loadings. The favorable properties of an La2O2CO3 surface-coating can benefit industrial catalyst synthesis, increasing the surface metal concentration compared with traditional La-based Al2O3 beads and pellets.